Pengaruh Posisi Penyemprotan Bahan Bakar Gas Lpg Pada Intake ManifoldTerhadap Konsumsi Bahan Bakar Pada Mesin Bensin Empat Langkah Satu Silinder (Honda Supra X) - Nuarsa, I Made; Mara, I Made; Riskon, Riskon (Dinamika Teknik Mesin, 2012)
One of major sources of air pollution is the result of combustion exhaust gases of automotive engines. As it is known that the process of fuel combustion from motor fuel produces exhaust gases which theoretically contain elements of CO, NOx, HC, CO2, H2O and N2, where many of which are polluting the surrounding environment in the form of air pollution. The use of LPG fuel for gasoline engine can be done by adding a piece of equipment called a conversion kit. In this study the fuel in the LPG gas injected in the intake manifold with some variation of spin injection with 3000 rpm, 4500 rpm and 6000 rpm for each transmision rate (Neutral s / d Gear 4). The result showed that the injection of fuel gas LPG in the rear position (P3) in getting a decrease in fuel Consumtion (FC) is optimal compared to other injection position (P1, P2). In addition the maximum fuel. Consumtion obtained at transmission rate at each round of variation mesin. Lowes CO emission levels found in LPG fuel injection in the rear position (P3) on the engine rev 3000 rpm kadar CO2 in round 3000 engine rpm optimum obtained from the use of LPG gas fuel injection in the rear position (P3) fornearly all transmision levels. Lowest HC emission values obtained on the location of the feul gas injection LPG rear position (P3) at 3000 rpm rotation at the 4th gear.